Inequality in the Development of the Virtual YouTube Industry in Indonesia Year 2020-2023 As Impact Investment Done by Hololive Production - Pakusadewo, Respati; Situmeang, Nurmasari (Universitas Negeri Semarang, 2024)
The aim of this research is to find out the impact of foreign corporation investment in the field of Virtual YouTubing in Indonesia and to look at the Virtual YouTubing sector development on the global creative economy and its development in Indonesia. The collection techniques used to gather the data were literature study, documentation study, and conducting interviews. The The results of this research show that Hololive Production is superior in several ways compared to local companies in Indonesia, amongst them are resources such US technology and facilities, and a stark contrast in the mindset of the people of Indonesia and Japan about the reception towards the Virtual YouTube industry. This research found that from the period 2020 to 2023, the VTubing industry in Indonesia only experienced growth but did not experience deeper and more comprehensive development.